Effect of niobium content on the microstructure and Young's modulus of Ti-xNb-7Zr alloys for medical implants. (November 2019) - Tan, Magdalen H.C.; Baghi, Alireza Dareh; Ghomashchi, Reza; Xiao, Wenlong; Oskouei, Reza H.
Abstract: New generation titanium alloys with low elastic moduli are promising materials for medical implants, particularly load-bearing orthopaedic implants. In this paper, the effect of niobium content on the microstructure and mechanical properties of new Ti alloys including Ti-23Nb-7Zr, Ti-28Nb-7Zr and Ti-33Nb-7Zr (wt%) is studied. Ti-23Nb-7Zr was found to mainly form α΄ and α″- phases, while both the Ti-28Nb-7Zr and Ti-33Nb-7Zr consisted of α″ and β-phases with an increased amount of β-phase in the alloy with 33 wt% of Nb. X-ray diffraction and microstructural analyses showed that the addition of Nb stabilises the β-phase in the solution treated condition with the depleting amount of α΄ and α″- phases. The hardness and Young's modulus values were highest in Ti-23Nb-7Zr which is attributed to the high fraction of α΄- phase in this alloy. The Young's moduli achieved for the three alloys through nanoindentation were 35.9, 29.1 and 29.0 GPa, respectively. The new alloys are encouraging candidates for orthopaedic implants due to their low elastic modulus which can help inhibit stress shielding, although biocompatibility tests ( in-vitro and in-vivo ) are suggested for future work.